Effects of thermal acclimation on cable constants of the earthworm median giant axon - Dierolf, Brecknell M; Brink, Peter R (Comparative Biochemistry and Physiology Part A: Physiology, 1973)
1. 1. The influence of thermal acclimation on cable constants of the median giant axon of earthworms, Lumbricus terrestris L., has been studied using standard intracellular stimulating and recording techniques. 2. 2. Acute cooling of axons from warm-acclimated worms resulted in changes in cable constants, some of which were partially compensated for (reversed) after cold acclimation. 3. 3. Of special interest is the relative behavior of specific axoplasm resistance in response to acute temperature change in warm- and cold-acclimated worms. 4. 4. The results suggest that thermal acclimation alters the properties of the axoplasm and that the resulting changes in cable constants contribute to compensatory adjustments in nerve conduction velocity after acclimation. © 1973.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-729-100-690-253 tex.type: [object Object]
Keywords: Lumbricus terrestris L.; Thermal acclimation; dept.bio; earthworm nerves; nerve acclimation; nerve cable properties; temperature-nerve